2012
DOI: 10.1136/annrheumdis-2012-201324
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of switching to alternative tumour necrosis factor (TNF) antagonists versus switching to rituximab in patients with rheumatoid arthritis who failed previous TNF antagonists: the MIRAR Study

Abstract: Optimal treatment for patients with RA failing on treatment with TNF antagonists may include RTX. This study suggests that the improvement in DAS28 is larger in patients treated with RTX than in those treated with monoclonal anti-TNF agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 8 publications
3
22
0
3
Order By: Relevance
“…Estimates of effectiveness in this retrospective claims-based analysis were consistent with the results from two prospective studies that compared TNFi cycling vs switching to the non-TNFi rituximab 16,17. In these studies, switching from a TNFi to a non-TNFi improved clinical outcomes more effectively than TNFi cycling.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Estimates of effectiveness in this retrospective claims-based analysis were consistent with the results from two prospective studies that compared TNFi cycling vs switching to the non-TNFi rituximab 16,17. In these studies, switching from a TNFi to a non-TNFi improved clinical outcomes more effectively than TNFi cycling.…”
Section: Discussionsupporting
confidence: 77%
“…One observational study reported that clinical improvement with switching to a non-TNFi relative to TNFi cycling occurred in the subgroup of patients who discontinued the initial TNFi because of inefficacy, but not among those who switched therapy because of intolerance 16. The other study reported that the clinical benefits of switching to a non-TNFi were observed vs TNFi cyclers who switched to adalimumab or infliximab, but not when TNFi cycling to etanercept was included in the comparison 17. A recent presentation of the results from a randomized, interventional study of 292 patients with an inadequate response to the first TNFi reported that switching to a non-TNFi resulted in significantly better efficacy than TNFi cycling, and the observed superiority was consistent over time and across outcome criteria 36…”
Section: Discussionmentioning
confidence: 99%
“…A clinical interpretation of this observation might be that after the failure of a monoclonal anti-TNF antibody one could consider switching to ETA, but when a patient has failed ETA as first TNFi, the choice of a monoclonal antibody as second TNFi might not have the same potential to lead to a clinically significant improvement. Indeed, other studies have shown that in the latter case it might be more beneficial to change to a biologic of a different mechanism of action 29 30. This might imply an underlying mechanism that could explain this finding: as it is known, ETA competitively inhibits the binding of both TNF and lymphotoxin-α to cell surface TNF receptors, rendering TNF biologically inactive,31 while INF and ADA bind and neutralise both soluble and membrane-bound TNF but not lymphotoxin.…”
Section: Discussionmentioning
confidence: 95%
“…The MIRAR study and real-life data indicate that switching to RTX is a successful treatment option for patients with RA failing on TNF antagonists 12,14,15…”
Section: Rtx In Ramentioning
confidence: 99%